Implementasi Algoritma You Only Look Once (YOLOv8) untuk Mendeteksi Pelanggaran Lalu Lintas Berupa Tidak Menggunakan Helm (Studi Kasus di Jatiasih, Bekasi) - Poerwandono, Edhy; Barronzoeputra, Gaoeng Qalbun (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2024)
This research aims to implement the You Only Look Once (YOLO) algorithm in detecting traffic violations in the form of riders who do not use helmets in Jatiasih, Bekasi. The problem studied is the high number of violations in the form of riders who do not use helmets which play a vital role in protecting riders from danger. The expected solution is the development of an automatic detection system that is able to identify this offence with a high level of accuracy. The object of the research is motorcyclists in Jatiasih, Bekasi. The research method used includes applying the YOLO algorithm to video recordings from surveillance cameras at several monitoring points. Video data processing is done by a laptop and YOLO algorithm-based software. The results of this research are expected to support law enforcement efforts, increase awareness of helmet use, and improve road safety by building an automatic detection system that can identify offences such as not wearing a helmet. The results of this research will show how effective the YOLO algorithm is for spotting traffic offences.